Enhancing productive collaboration competence strategies in indonesian language learning: a conceptual approach - Khoiri, M; Kusyairi, Kusyairi (2023)
This article aims to explore and elaborate on an effective conceptual approach to enhancing productive collaborative competence in Indonesian language learning. The primary objective is to provide practical guidance for educators in integrating language instruction with collaborative training, thereby creating a holistic learning environment that is relevant to the demands of the modern world. The research methodology employed in this study involves meticulous literature analysis to identify a conceptual framework that supports the integration of language learning and collaborative training. In doing so, it encompasses research findings and practical experiences in teaching Indonesian to illustrate the implementation of this strategy in the classroom. The researcher offers a comprehensive perspective on the development of productive collaboration competence within the context of language learning. The article discusses the concept of productive collaboration competence and underscores the significance of integrating language learning with collaborative training. The researcher considers how task-based learning can be used to stimulate student collaboration, foster language skills development, and promote cultural understanding within the context of the Indonesian language. Additionally, the researcher explores how educators can create an environment conducive to this type of learning, enabling students to learn while collaborating and interacting effectively.